(untitled) (International Journal of Built Environment and Sustainability, 2025)
In recent years, mental health has emerged as a growing concern within residential settings of developing countries, where fast urbanization and environmental stressors have contributed to a rise in psychiatric disorders. Among the various factors influencing public health, the quality of the urban environment plays a significant role in supporting or undermining the mental well-being of residents. Within this broader context, this article explores the relationship between urban environmental conditions and mental health outcomes, focusing on the Sangi neighborhood in Bushehr City, Iran. By examining this specific case, the study seeks to uncover the key environmental and social variables that influence mental health in urban residential areas. This study employs descriptive-interpretive qualitative method, which has led to practical strategies for Sangi neighborhood. Twenty-four variables relevant to the subject were identified from reliable, up-to-date, and pertinent sources. These variables were then entered into MicMac software for cross-effects analysis. Pairwise comparisons between the variables were conducted using the Delphi method, with the involvement of five experts. The findings show that noise pollution and congestion, safety and security, participation in neighborhood affairs, sense of attachment to the neighborhood, social interactions, facilities and amenities within neighborhood, residents’ sense of happiness, vitality and diversity, social capital, adequate housing and social unity are among the effective and controllable key factors affecting the mental health of residents in Sangi. Also, variables such as cleanliness and natural light are known as effective and uncontrollable driving factors of mental health. Ultimately, the study formulates necessary operational strategies to improve the quality of the identified variables in Sangi neighborhood in Bushehr. The findings of this study can be applied on similar case studies in Iran and other countries.